Peningkatan Kemampuan Komunikasi Publik melalui Pengembangan Bahan Ajar Menulis Teks Ceramah bagi Siswa SMA Kota Semarang - Wafiah, Saidatul; Suwandi, Suwandi; Maharani, Nazla (Mu'ashir: Jurnal Dakwah dan Komunikasi Islam, 2023)
This study aims to develop teaching materials for writing lecture texts for high school students in Semarang City. The method used is Research and Development (R&D) to produce teaching materials for writing lecture texts using the brainstorming method. Data were collected through interviews, questionnaires, and documentation. The results showed that the results of expert validation obtained a score of 80.75, which means that the teaching materials for writing lecture texts with the brainstorming method are suitable for use. The average value of the limited trial results of writing lecture texts at MA AL Asror Semarang and MA Riyadussholihin was 91.25. Based on the results of the overall assessment, an average score of 4.03 was obtained with a feasibility level of 80.65% categorized as "good", the presentation aspect of the book obtained an average score of 4.07 with a feasibility level of 81.4% categorized as "good", the language aspect obtained an average score of 4.08 with a feasibility level of 81.6% categorized as "good", and the graphical aspect the average score obtained was 4.09 with a feasibility level of 81.8% categorized as "good". Thus it can be concluded that the textbook developed is declared "feasible" for use.